Avaliação de desempenho de fornecedores em cadeias de suprimentos utilizando a teoria da resposta ao item - Santos, Kathyana Vanessa Diniz (2017)
An adequate selection of suppliers can make a difference in the future of organizations, lowering operating costs, improving product quality and enabling quick responses to customer demands. In the current business context of supply chains, the appropriate choice of suppliers is essential for good management and maintenance and improvement of competitive advantages. Therefore, the objective of this dissertation is to develop a method to evaluate suppliers performance in the context of supply chains, using item response theory (IRT). To achieve this goal, 60 supplier performance aspects, covering seven dimensions (cost, time, quality, flexibility, innovation, reputation/ industry experience and sustainability), were considered in the formulation of a questionnaire with 67 items to evaluate supplier performance. The questionnaire made possible the evaluation of 243 supply links of companies across different sectors and 14 Brazilian States. The evaluation results of the 243 supply links were analyzed using IRT’s Graded Response Model (GRM). GRM establishes a difficulty parameter for each category of the presented items, defining levels of performance in an interpretable scale that indicates the aspects served by each evaluated relationship and informs what aspects the company evaluated still needs to evolve in. Depending on what the client company expects and prioritizes in the performance of its suppliers, it can associate scale levels (and the presence and/or absence of certain aspects) with decisions about what to do in the relationship with the supplier company (deepen relationship, request changes in behavior or end relationship, for example).